Industrial smart product-service systems solution design via hybrid concerns - Zheng, Pai (2020)
Enabled by the third and fourth waves of Information Technology (IT) innovation, together with the sustainable concerns towards a circular economy, manufacturing industries are shifting rapidly towards a service-oriented paradigm in the smart, connected environment, i.e. smart product-service systems (Smart PSS). Owing to its unique characteristics, it reshapes the solution design (product-service design) with several hybrid concerns. This research, as an explorative study, underlines three general ones at the macro-level, i.e. design and redesign as an overall value generation process (hybrid design), human and machine intelligence integration (hybrid intelligence), and technical and business innovation (hybrid value). Accordingly, novel design methods, intelligent systems, and value co-creation models are envisioned at the micro-level to assure industrial Smart PSS solution design success. To make our visions concrete, two prospective application scenarios leveraging abovementioned hybrid concerns are given at last. It is hoped this work can contribute to the future directions of this interdisciplinary research area, and offer insightful guidance to industrial companies in their solution design process with profitable outcomes.